On the type of Genista terniflora (Loteae-Leguminosae) - Ferrer Gallego, Pedro Pablo (Acta Botanica Malacitana, 2023)
The name Genista terniflora (Anthyllis terniflora) is neotypified. A specimen preserved in the herbarium of the Royal Botanical Garden of Madrid (at MA) and collected by Cavanilles in 1792 is selected as the neotype.